Climate risk perception and adaptation of tourism sector in China. (March 2022) - Hu, Qiangsheng; Becken, Susanne; He, Xiaorong
Abstract: Understanding the perceptions of climate change by those working in tourism greatly supports development of adaptation measures in destinations. However, limited evidence of either perceptions or tourism adaptation measures is available from China. Building on protection motivation theory, this study explores how Chinese working in tourism perceive climate change and what their adaptation intentions are. The study demonstrates that the current level of climate risk perception is relatively high, and people feel informed. The results indicate that (1) Information plays an important role in risk and adaptation appraisals; (2) Individuals are more likely to take adaptation measures if they perceive greater climate risks and have higher adaptive capacity; (3) An increase in adaptive incentives would generally support an increase in adaptation appraisal; (4) Providing greater adaptive incentives will motivate tourism staff to take actions and implement adaptation measures. The findings have implications for adaptation policies and strategies in destinations. Highlights: A first attempt to examine Chinese tourism employees and managers' climate change perceptions and adaptation intentions. The current level of climate risk perception is relatively high, and people feel informed. Respondents are more likely to take measures if they perceive greater climate risks and have higher adaptive capacity. Providing more adaptive incentives will motivate tourism staff to take actions and implement adaptation measures.